Zina sebagai Takdir: Analisis Kitab al-Minhāj fī Syarḥ Ṣaḥīḥ Muslim Karya Imam al-Nawawi - Saputra, Doni (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
Zina is an act that is strictly prohibited in Islam. In a hadith, there is a narration that states that Allah SWT has destined some of Adam's children to commit adultery. However, in the Qur'an itself, Allah SWT forbids the act of adultery. Not only is it forbidden to approach her, but it is also considered a heinous act. So how is it possible for humans to avoid committing adultery, if Allah SWT has already destined some people to be adulterers? This research aims to uncover the meaning of the phrase "zina as destiny" through an analysis of the commentary on hadith using qualitative research methods and a literature-based approach that focuses on the literature of the commentary on hadith by Imam al-Nawawi as the main reference. Furthermore, the selection of Imam al-Nawawi as the focus of this study is due to his status as a hadith scholar who is widely referenced. From the research conducted, it concludes that the concept of adultery as fate here is divided into two categories: major adultery and minor adultery. Major adultery involves sexual intercourse, while minor adultery consists of various forms such as adultery of the eyes, ears, mouth, and others. Due to this, it is challenging to avoid these forms of adultery in today's era, where access to such acts is very easy. It seems that the words of the Prophet Muhammad (peace be upon him) are very relevant to the current situation, as every child of Adam will be affected by adultery when viewed through the lens of the phenomena occurring today.